Afforestation improves thermal comfort in urban areas: The case of Juazeiro do Norte, Ceará (Research, Society and Development, 2020)
Urban spaces in Brazil have been changing over time, cities have become an artificial medium and have caused extensive changes in the urban climate. The removal of the vegetation cover and the properties of the materials that constitute the modified surfaces such as asphalting increased the surface runoff, decreased humidity and modified the wind speed, increasing the temperature and causing thermal discomfort.  In this context, it is important that alternatives be given to mitigate the impacts generated. The aim of this article is to verify the oscillations of the climatological variables: minimum temperature, maximum temperature, relative humidity and wind speed in two neighborhoods of the city of Juazeiro do Norte/CE. To carry out the research, measurements were made in the Pirajá Neighborhood and in the Timbaúbas Ecological Park. Twelve points were selected to perform the collections. The Thermo-Higro-Anemometer portable digital brand Instrutherm, model THAR-185. Data were collected in The following months: August, September, October, November and December 2019, because it is the hottest period of the year. The results showed that the presence of afforestation interferes with climatic variables and plays an essential role in improving thermal comfort.